Pivot for Success - Hilliard, Amy (Ascent Audio, 2021)
Pivot for Success tells business leader and entrepreneur Amy Hilliard's stories of success, struggle, and sustainability to inspire you to become resilient. Hilliard offers her hard-won perspective on what it takes to "make it" in American business and in life. She talks about the tough stuff, the stuff that most people who rise to her level of accomplishment aren't eager for others to know. Few women, and few women of color, have created multi-million-dollar brands in senior corporate positions, legendary entrepreneurial environments, and start-ups. Hilliard's fearless honesty in revealing her experience can help you find your way forward, even if you face obstacles in today's business environment. While Hilliard is a Harvard Business School graduate, Pivot for Success contains lessons not taught in school. Her perspective on success and the failure it often takes to succeed are invaluable. In this book, you will learn the 10 Pivot Points that have led Hilliard to where she is today, including Purpose, Passion, Perseverance, Positivity, Priorities, and more. No matter who you are or where you are in your life's journey, you'll need to gain vision, shift your energy, and make moves in order to get where you're going. Through Pivot for Success, you'll find that you can succeed, even when you think you've lost it all.
Online resource; Title from title page (viewed August 31, 2021)
Keywords: Audiobooks; Livres audio